TUGAS DAN FUNGSI SATUAN PERAWATAN TAHANAN DAN BARANG BUKTI (SAT SAHTI) DALAM PENANGANAN BARANG BUKTI TINDAK PIDANA DI POLRES BUTON UTARA - La Ode , Ali Mustafa; Harjo, Rusdin (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2025)
This study aims to determine the implementation of supervision of detainees and evidence in the jurisdiction of the North Buton Police Resort and to determine the obstacles and efforts to overcome obstacles in the implementation of supervision of detainees and evidence in the North Buton Police Resort. This study is a descriptive study, the location of this research is at the North Buton Police Resort, data analysis in this study uses a qualitative method, namely using information or data that has been collected and presented in the form of descriptions by combining library research and field research so that a conclusion can be drawn in order to obtain a complete and systematic picture regarding the Management of Evidence in the Criminal Case Settlement Process. As for the results of this study, it can be concluded that the implementation of evidence management is guided by Police Regulation No. 10 of 2010 concerning Evidence Management Procedures: Implementation of evidence management at the North Buton Police Department includes receipt, storage, safeguarding, maintenance, release, destruction, administration, and reporting. The implementation of evidence management at the North Buton Police Department complies with applicable police legal regulations, ensuring that all items confiscated by investigators are stored at the SAT TAHTI (Detention Unit) in the evidence storage warehouse. However, the implementation of evidence management continues to face challenges, including a lack of police personnel on duty, inadequate facilities and infrastructure, and a lack of experts within the SAT TAHTI organizational structure.